Fenomena Rendahnya Kinerja Karyawan Bagian Produksi Laksana Home Metal Industri Bandung - Sundawa, Irfan Noor; Sumiyati, Sumiyati; Purnama, Ridwan (Universitas Pendidikan Indonesia, 2018)
The purpose of this study is how much influence the reward system for performance, work discipline on performance and reward systems and work discipline on employee performance. The type of research used is descriptive and verification. The method used in this research is explanatory survey with saturated sample technique and the number of respondents is 71 people. The data analysis technique used in this study is path analysis. The findings of the study on testing the hypothesis are known that reward systems and work discipline affect employee performance simultaneously. Differences found in the object of research, research period, measuring instruments and research results. The author also adds theories from foreign journals and foreign books